### Home > A2C > Chapter 4 > Lesson 4.1.3 > Problem 4-39

4-39.

Solve each of the following equations

*without using the Quadratic Formula.*Homework Help ✎*y*^{2}− 6*y*= 0*n*^{2}+ 5*n*+ 7 = 72t

^{2}− 14*t*+ 3 = 3Zero is one of the solutions of each of the above equations. What do all of the above equations have in common that causes them to have zero as a solution?

Notice: *y* is a common factor.

*y*(*y* − 6) = 0

*y* = 0, 6

Start by subtracting 7 from both sides.

Solve by factoring.

See part (b).

See part (b).

Look at all of the common factors.